Factors that Influence the Financial Literacy on Micro Small and Medium Entreprise - Isna Ardila; Hastina Febriaty; Rini Astuti (Journal of International Conference Proceedings (JICP), 2021)
Provide a study and analysis of the factors of financial literacy related to the financial management of MSMEs in the city of Medan as the purpose of this research. This objective is based on the existing conditions in which MSMEs activities run without relying on information and financial management that is arranged in an orderly and orderly manner. The research approach used is associative. Primary data as the type in this study were sourced from questionnaires and interviews. The population used is the perpetrators of SMEs in the food and beverage industry sector in the city of Medan, amounting to 120 respondents, using purposive sampling technique in sampling, then obtained as many as 100 samples used in this study as respondents. Each questionnaire statement collected and used as data in this study will be measured by validity and reliability tests. The data analysis method uses Confirmatory Factor Analysis (CFA) using the SEM (Structural Equation Model) structural equation model. Evaluation of the structural equation model using the t statistic and p value parameters. This study based on the test results found that three variables of financial literacy, including financial behavior, financial socialization, and bookkeeping systems positively and significantly affect it.